2012
DOI: 10.1111/j.1095-8649.2012.03307.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of the mandibular, hyoid arch and gill arch skeleton in the Chinese barb Puntius semifasciolatus: comparisons of ossification sequences among Cypriniformes

Abstract: The morphogenesis and sequence of ossification and chondrification of skeletal elements of the jaws, and hyoid arch and gill arches of Puntius semifasciolatus are described. These data provide a baseline for further studies and enable comparisons with other described cypriniforms. Some general patterns of ossification in the hyoid arch and branchial arches in cypriniforms were notable. First, the overall development is from anterior to posterior, with the exception of the fifth ceratobranchial bone, which ossi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
3
8
0
Order By: Relevance
“…In the three species examined, all epibranchials 1–4 appear early in development, at 5.6 mm SL (4 DPH) in P. argenteus , 7.7 mm SL (3 DPH) in L. alexandri , and 3.8 mm SL (3 DPH) in P. corruscans . This pattern, in which all four epibranchials appear early in development either simultaneously or within a short time interval, has also been reported for species of other ostariophysan lineages, such as Gonorynchiformes (Chanidae [42], [43]), Cypriniformes (Cyprinidae [44]–[48], Catostomidae [49]), Characiformes (Characidae [26], [50]), and Siluriformes (e.g. Pangasiidae and Schilbidae [51]; Ariidae and Plotosidae [52]; Bagridae [53]; Clariidae and Heteropneustidae [54]; Clariidae [55], [56]; Callichthyidae [57]; Loricariidae [58]), as well as in a representatives of the closely related Clupeiformes (Clupeidae [59]).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…In the three species examined, all epibranchials 1–4 appear early in development, at 5.6 mm SL (4 DPH) in P. argenteus , 7.7 mm SL (3 DPH) in L. alexandri , and 3.8 mm SL (3 DPH) in P. corruscans . This pattern, in which all four epibranchials appear early in development either simultaneously or within a short time interval, has also been reported for species of other ostariophysan lineages, such as Gonorynchiformes (Chanidae [42], [43]), Cypriniformes (Cyprinidae [44]–[48], Catostomidae [49]), Characiformes (Characidae [26], [50]), and Siluriformes (e.g. Pangasiidae and Schilbidae [51]; Ariidae and Plotosidae [52]; Bagridae [53]; Clariidae and Heteropneustidae [54]; Clariidae [55], [56]; Callichthyidae [57]; Loricariidae [58]), as well as in a representatives of the closely related Clupeiformes (Clupeidae [59]).…”
Section: Resultssupporting
confidence: 70%
“…This suggests a putatively heterochronic event in epibranchial formation in Polypterus , since the epibrachial of many actinopterygians appear early in ontogeny, just after the formation of all ceratobranchial elements (e.g. [42], [48], [49], [118], current study).…”
Section: Resultsmentioning
confidence: 64%
“…Overall, elements of the skeleton develop at smaller sizes in C. nebulosus than in S. ocellatus . This is not surprising as it is generally observed that smaller species tend to develop quicker than larger bodied, closely related species; a concept first proposed by Reiss () and observed in the skeletal development of Puntius semifasciolatus by Block and Mabee (). Despite the difference in overall size at first appearance of skeletal elements between C. nebulosus and S. ocellatus , no major differences are observed between the sequences of ossification for the two species by region (Figs and ), other than relatively minor differences involving the switching of one or two bones in the order of the sequence (see comparisons between ossification sequence of S. ocellatus and C. nebulosus ).…”
Section: Discussionmentioning
confidence: 62%
“…; Engeman et al . ; Block and Mabee ; Engeman and Mabee ) may be indicative of the significance of this element to the biology of cypriniform fishes in general.…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of the danionine cyprinids Paedocypris (Britz & Conway, ) and Danionella (Britz & Conway, ) and the characiform Priocharax (Mattox, Britz, & Toledo‐Piza, ), we were interested to see if the bones that fail to ossify in Barboides are bones that otherwise form in the later stages of skeletal development in closely related nonminiature cyprinine relatives. Few developmental studies exist for cyprinines and those which are available focus only on the cranium ( Barbus barbus , Vandewalle, Focant, Huriaux, & Chardon, ) or the viscerocranium ( Barbodes semifasciolatus , Block & Mabee, ) and therefore we compiled the ossification sequence of the entire skeleton of the African cyprinine ‘ Barbus ’ holotaenia as our reference sequence (Figure ). Following the approach developed by Britz and Conway (), we mapped the bone absences in Barboides onto the ossification sequence derived from ‘ B .’ holotaenia .…”
Section: Discussionmentioning
confidence: 99%